Preliminary Assessment of The Population Structure and Habitat Characteristics of Javan Langur (Trachyphitecus auratus É. Geoffroy, 1812) in Natural Reserve Watangan Puger - Asyrofi, Muhammad; Sulistiyowati, Hari; Wimbaningrum, Retno (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2022)
Javan langur (Trachypithecus auratus É. Geoffroy, 1812) is categorized by IUCN as a vulnerable primate species since 2008 and protected under 2018 LHK regulation. They can be found across Java Island, also in the Watangan Puger Nature Reserve (WPNR), East Java. There is no information about the population and habitat characteristics of Javan langur in WPNR except their existence. This research study aims to estimate the population structure, population density, and habitat characteristics of the Javan Langur in the WPNR, within the area of 2.6 ha. Three concentration points for daily observations were determined for 3 days. A combination of concentration count with scan sampling observation method at intervals of 30 minutes every hour of observation was done to get the data of density, position, population structure, and plant species preferred by Javan langurs. The important value, diversity Shannon-Wiener index, and plant species preferred were also analyzed. There are 26 population composed of two groups of the Javan langur occupying an area of 1,118 ha (43%). The population size estimatation for the first group was 17 individuals with a population density of 15.17 individu/ha, while that for the second group was 9 individuals with a population density of 8.02 individu/ha. The twenty-six Javan langurs are composed of complete age structure such as adult 69%, sub-adult 15%, and infant 16%. The Javan langur population was mostly found in the vegetation structure of Syzygium jambos (jambu hutan) to Pithecellobium dulce (asam manila) (IV = 45.47 to 3.88). Total 24 tree species are found in WNPR, most of the trees are used by the Javan langur as food and cover. The tree community in WPNR has medium diversity with value of 2.28. Furthermore, the Javan langur prefer Artocarpus elasticus (bendo) and Syzygium jambos (jambu hutan) at the upper strata (> 15 meters) than other trees and strata. Most of them are actively walking or jumping (locomotion) during the activity observed at the tree community.